2007
DOI: 10.1159/000104744
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Obsessive-Compulsive Disorder: The Different Impact of Obsessions and Compulsions

Abstract: Background: Patients with obsessive-compulsive disorder (OCD) are troubled by repeated obsessions and/or compulsions, which seem senseless and frequently repugnant. Objective: The study examines the differential impact of obsessions and compulsions on the quality of life (QoL) of patients with OCD. Methods: Seventy-five patients (43 females, 32 males) between 21 and 62 years old with OCD (ICD 10 F42.0–F42.2) were recruited from the outpatient clinic for anxiety disorders at the Department of Psychiatry of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 85 publications
(66 reference statements)
3
24
0
Order By: Relevance
“…48 Even with relatively mild mean scores of depression and anxiety symptoms, their additional impact on OCD may increase the patient's burden and, probably, of their families. 25 More specific analyses of QoL of these patients will be described in future papers, regarding clinical aspects that can have different impact, such as obsessions or compulsions, as suggested by Stengler-Wenzke et al 49 The CTOC participants are confident that their main goals have been successfully achieved so far. Relevant clinical data have been systematically and uniformly collected, a large database for collaborative studies has been built, graduate and post-graduate students are receiving research training in this field, and expert groups are under continuous development throughout the country.…”
Section: Discussionmentioning
confidence: 96%
“…48 Even with relatively mild mean scores of depression and anxiety symptoms, their additional impact on OCD may increase the patient's burden and, probably, of their families. 25 More specific analyses of QoL of these patients will be described in future papers, regarding clinical aspects that can have different impact, such as obsessions or compulsions, as suggested by Stengler-Wenzke et al 49 The CTOC participants are confident that their main goals have been successfully achieved so far. Relevant clinical data have been systematically and uniformly collected, a large database for collaborative studies has been built, graduate and post-graduate students are receiving research training in this field, and expert groups are under continuous development throughout the country.…”
Section: Discussionmentioning
confidence: 96%
“…Similar data have been reported by previous studies conducted with adults. 29,34,35 These findings may be explained by the fact that, even though quality of life is considered a multifactorial construct, the different features analyzed by each of the domains are probably also present in the impairment associated with depression episodes, with a potential overlap between depression characteristics and the quality of life construct.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that obsessive-compulsive disorder can have adverse effects on the QOL of relatives of patients with obsessive-compulsive disorder. Family members report finding themselves accommodating to the illness and becoming involved in the patients' rituals, often impairing their own everyday life [35,36]. Family members, including siblings, report a reduced QOL, high levels of family distress, depression, anxiety, feelings of frustration, anger, and guilt [37,38].…”
Section: Discussionmentioning
confidence: 99%